2020
DOI: 10.1186/s12917-020-02588-w
|View full text |Cite
|
Sign up to set email alerts
|

Persistent domestic circulation of African swine fever virus in Tanzania, 2015–2017

Abstract: Background African swine fever (ASF) is a highly fatal viral hemorrhagic disease of domestic pigs that threatens livelihoods and food security. In Africa, ASF virus (ASFV) circulates in sylvatic (transmission between warthogs and soft argasid ticks) and domestic (transmission between domestic pigs) cycles, with outbreaks resulting from ASFV spill-over from sylvatic cycle. A number of outbreaks were reported in different parts of Tanzania between 2015 and 2017. The present study investigated ASFV transmission p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The genotype X was recovered from domestic pigs in 1950 in Kenya [ 15 ], since then, it was regularly reported to circulate and cause ASF outbreaks in Kenya [ 15 , 16 , 21 , 23 ], Uganda [ 21 , 23 ], Tanzania [ 22 , 23 , 61 , 62 ], Burundi [ 22 , 23 , 64 ], and DRC [ 51 ]. Recent molecular studies have reported high genetic similarity at three genomic regions of ASFV (p72, CVR and I73R-I329L ) between the ASFV p72 genotype X strains responsible for ASF outbreaks in 2016 in Kagera region in Tanzania [ 62 , 64 ], the 2018 ASF outbreak in Rutana region in Burundi [ 64 ], and the ASF outbreak that occurred during December 2018 to January 2019 in South Kivu province of the DRC [ 51 ]. Commercial traffic and cross-border movements of domestic pigs and pork products were speculated as the main drivers of the ASFV spread between DRC, Burundi, and Tanzania [ 51 , 53 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The genotype X was recovered from domestic pigs in 1950 in Kenya [ 15 ], since then, it was regularly reported to circulate and cause ASF outbreaks in Kenya [ 15 , 16 , 21 , 23 ], Uganda [ 21 , 23 ], Tanzania [ 22 , 23 , 61 , 62 ], Burundi [ 22 , 23 , 64 ], and DRC [ 51 ]. Recent molecular studies have reported high genetic similarity at three genomic regions of ASFV (p72, CVR and I73R-I329L ) between the ASFV p72 genotype X strains responsible for ASF outbreaks in 2016 in Kagera region in Tanzania [ 62 , 64 ], the 2018 ASF outbreak in Rutana region in Burundi [ 64 ], and the ASF outbreak that occurred during December 2018 to January 2019 in South Kivu province of the DRC [ 51 ]. Commercial traffic and cross-border movements of domestic pigs and pork products were speculated as the main drivers of the ASFV spread between DRC, Burundi, and Tanzania [ 51 , 53 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ASFV p72 genotype IX was recovered from domestic pigs and warthogs. This genotype is described as the most predominant in Uganda and Kenya [ 42 ], but also, it was described in DRC [ 50 , 53 ] and Tanzania [ 56 , 62 ]. Although associated with lethal ASF outbreaks [ 21 , 47 , 48 ], an increasing number of studies reported the genotype IX in asymptomatic domestic pigs in Tanzania [ 56 ], DRC [ 50 ], Uganda [ 44 ], and Kenya [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations